Dietary practices and menu analysis of Singapore's childcare centres - Ratnala Sukanya Naidu (2008)
This study surveyed the dietary practices in childcare centres in Singapore and evaluated their menus.It also sought to identify the primary menu planner and meal preparer and their levels of training.